Effect of Proper Treatment on Mineral Oils - Felix, Stephanie Azlyn Anak; Din, Muhamad Faiz MD (Universitas Pendidikan Indonesia (UPI), 2023)
For over a century, a transformer act as a crucial part of the high voltage system. This also acts as an energy alteration device that is used to step-up and step-down voltage for power distribution from power generation to the consumers. Maintaining a transformer is important since a single mistake can lead to a vast amount of problems in a high voltage system in terms of cost. Thus, nowadays, many researchers study the important parts of a transformer, making it to function more effective. One of the studies involves improving treatment in the insulation medium of transformers to improve its function and performance. Here, the focus of this experiment was to study the effect of proper treatment on mineral oil in terms of electrical properties as an insulator in the transformer. The drying process was the main concern in this experiment. Parameters such as AC breakdown voltage, Tan Delta value, Raman measurement, resistivity, and relative permittivity were particularly measured. Origin software was used to analyze the data obtained from the experiment. The results expected from the experiment is that the proper preparation plays the role in tuning the AC breakdown voltage.